Cancer and liver cirrhosis: implications on prognosis and management - Pinter, Matthias (ESMO Open, 2016)
Liver cirrhosis, the end-stage of every chronic liver disease, is not only the major risk factor for the development of hepatocellular carcinoma but also a limiting factor for anticancer therapy of liver and non-hepatic malignancies. Liver cirrhosis may limit surgical and interventional approaches to cancer treatment, influence pharmacokinetics of anticancer drugs, increase side effects of chemotherapy, render patients susceptible for hepatotoxicity, and ultimately result in a competitive risk for morbidity and mortality. In this review, we provide a concise overview about the impact of liver cirrhosis on the management and prognosis of patients with primary liver cancer or non-hepatic malignancies.